Impact of Starvation, Refeeding of Freshwater Fish Channa punctatus Via Comparatively Protein Level Investigation on Target Tissues - Dar, Zubair S.; Dongre, S. B.; Pawar, S. S.; Wani, Mashooq A. (Journal for Research in Applied Sciences and Biotechnology, 2022)
Using Lowry's approach, the current study investigated how starvation and refeeding affected the amount of protein in various tissues of the freshwater fish Channa panctatus (1951). The fish were categorised into two groups, the first group had normal feedings, while the second was denied food for periods of 7, 14, 21, and 28 days respectively. Notably, the previously starved fish were fed again. Fish show a significant rise in protein levels relative to normal following feeding because prolonged starvation causes a steady drop in tissue protein levels.